Android encryption system - Mok, Jun Wen (Nanyang Technological University, 2021)
Android users have been provided with two different types of disk encryption methods since Android 4.4. The older encryption method is called “Full Disk Encryption” (FDE) which encrypts the /data portion of the disk. The drawback to using FDE is that the disk is not accessible until the user provides their credentials which means multiple critical functions are not available. “File Based Encryption” (FBE) was introduced in Android 7.0 which allows files to be encrypted independently. This allows critical phone functions that do not require high security to be accessed before the phone is unlocked which solves the drawback of FDE.